Ir. Ts. Dr. Norazlianie produces pure butter in food technology - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 23 August 2023 - The production of dairy-based products in Malaysia is less than five per cent in the country and the rest depends on imported products.